Improving Education and Training Quality by Implementing New Developing Methods - B, Yunusov Kh.; Yu.A, Balakin; A, Yunusova D. (International Journal of Psychosocial Rehabilitation, 2020)
The work outlines a new technique used in the classroom of the faculty of advanced training of teachers of technical and humanitarian disciplines. The methodology is based on original ideas to improve the quality of students’ knowledge as a result of their development.